Boron adsorption in semiarid Mediterranean soils under the influence of background electrolytes - S. Fatnassi; M.B. Almendro Candel; J. Navarro Pedreño; I. Gómez Lucas; M. Hachicha (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Boron is a micronutrient of high importance, both for plant development and normal growth. The range between boron deficiency and toxicity is very narrow, which makes boron unique among the essential micronutrients. Boron adsorption is one of the most important factors determining the release and fixation of this micronutrient, though its adsorption has not been widely studied in semiarid Tunisian soils. This study aims to improve knowledge of B adsorption process in calcareous salt-affected soils in semiarid areas. It equally focuses on the type of cation (monovalent and divalent) in function of the soil texture and time of shaking. These three latter factors influence boron adsorption, which also influence the availability for plants.METHODS: A study was carried out on boron adsorption at different shaking time intervals (1, 3, 6 and 9 hours) in two soils of different textures in the absence and  presence of different background electrolytes solutions (0.02 N CaCl2, 0.02 N MgCl2 , 0.02 N sodium chloride and 0.02 N potassium chloride.FINDINGS: The soil-A (clay loam) adsorbed more boron than soil-B (sandy loam). Boron adsorption was the highest in Soil-A under the presence of potassium chloride, close to the mean values given when using calcium chloride. In Soil-B, it was found with calcium chloride background electrolyte. Minor boron adsorption was observed in both soils when boric acid solution was used without background electrolytes. Adsorbed boron showed significant differences with the shaking time in all treatments used with background electrolytes solutions, except for boron solution treatment without background electrolyte in both soils. As a comparison of divalent and monovalent cations, boron adsorbed content was higher with the solution containing calcium than in sodium chloride solution, due to the fact that calcium carbonate is an important boron adsorbing surface.CONCLUSION: This study reveals that the best conditions for maximum boron adsorption are defined by calcium chloride background electrolyte in this type of soil in a determined shaking time interval of 3 hours. This causes a low rate of boron assimilated by plants, which leads to the decrease of the crop yield and the agricultural production, and subsequently hurt the Tunisian national economy.